Research Progress of Green Volatile Corrosion Inhibitors - GUO Yipeng, YAN Hongbing, LI Yanling, XU Sen, NING Chunhua, ZHOU Di (Cailiao Baohu, 2024)
In recent years， with the continuous improvement of people’s awareness of health， environmental protection， and safety， as well as the implementation of relevant laws and regulations， higher requirements have been put forward in industry for volatile corrosion inhibitors that play a protective role in the production and application of metal products.Consequently， the use of some highly toxic and environmentally impactful volatile corrosion inhibitors has been restricted.Therefore， developing and promoting a new generation of environmentally friendly and safe vapor phase corrosion inhibitors is imperative.Additionally， the development and utilization of renewable resources constitute an important measure for the sustainable development of human society.Renewable resources， derived from natural animal and plant sources， particularly crops， fruits， vegetables and timber processing waste， are rich in natural antioxidants， preservatives and antimicrobial agents.They hold great potential for the development and utilization of vapor phase corrosion inhibitors.Currently， domestic and foreign researchers have conducted focused research on this new generation of green vapor phase corrosion inhibitors.In this paper， the history of volatile corrosion inhibitors was summarized， followed by a discussion on the current research of green volatile corrosion inhibitors， including amino acids， polyaspartate， plant compounds and plant extracts.The future development trend of green volatile corrosion inhibitors was then projected，aiming to provide necessary support for their industrialized application.